Reference generator for voltage controlled power conditioners - Terrazas, T. M. [UNESP]; Marafão, F. P. [UNESP]; Monteiro, T. C.; Giaretta, A. R.; Matakas, L.; Komatsu, W. (Institute of Electrical and Electronics Engineers (IEEE), 2011)
Voltage reference generation is an important issue on electronic power conditioners or voltage compensators connected to the electric grid. Several equipments, such as Dynamic Voltage Restorers (DVR), Uninterruptable Power Supplies (UPS) and Unified Power Quality Conditioners (UPQC) need a proper voltage reference to be able to compensate electric network disturbances. This work presents a new reference generator's algorithm, based on vector algebra and digital filtering techniques. It is particularly suited for the development of voltage compensators with energy storage, which would be able to mitigate steady state disturbances, such as waveform distortions and unbalances, and also transient disturbances, like voltage sags and swells. Simulation and experimental results are presented for the validation of the proposed algorithm. © 2011 IEEE.
Keywords: Dynamic Voltage Restorer; Phase-Locked-Loop; Positive Sequence; Uninterruptable Power Supply; UPQC; Digital filtering techniques; Dynamic voltage restorers; Electric grids; Electronic power conditioner; Power conditioners; Power supply; Reference generator; Steady state; Transient disturbances; Unified power quality conditioners; Vector algebra; Voltage compensators; Voltage reference; Voltage sags; Voltage-controlled; Waveform distortions; Algorithms; Circuit theory; Power electronics; Uninterruptible power systems; Videodisks; Voltage measurement; Voltage regulators; Power quality